Upaya KUA Lhoksukon Aceh Utara Dalam Meminimalisir Problema Nikah Liar - Dhiauddin Tanjung; Ramadhan Syahmedi Siregar; Teuku Islahuddin (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2022)
Illegal marriage is a strange phenomenon that is still intense in the Acehnese community. In fact, Islam has very clearly forbade any form of marriage that is carried out in secret in order to produce a harmonious family and social community. The occurrence of illegal marriages when the condition of the bride still has a nasab guardian is a practice that is allegedly in bad faith, one of which is because the husband still has a legal wife who does not agree to polygamy. There are also those who do illegal marriages because they want to find an alternative to their work which prohibits polygamy status. This reality is a reality that can harm many parties, both for family members and society. In response to this, the Lhoksukon KUA has implemented various policies so that the problem of illegal marriages can be minimized. This article belongs to field research with a qualitative approach. The methodology used is a phenomenological study of the actions of KUA Lhoksukon North Aceh. The results of the study concluded that the KUA Lhoksukon North Aceh carried out various activities to prevent illegal marriage by way of socialization and guidance to the community regarding the negative impact of illegal marriage.